Strategi Kepala Madrasah Tsanawiyah Negeri 1 Kota Gorontalo dalam Mengimplementasikan Pengembangan Kurikulum Merdeka - Ahudulu, Siswan; Yahiji, Kasim (Pascasarjana IAIN Sultan Amai Gorontalo, 2023)
This study aims to analyse the strategy of the madrasah head in implementing the independent learning curriculum at Madrasah Tsanawiyah Negeri 1 Gorontalo City and to analyze the obstacles and solutions in implementing the Merdeka Belajar curriculum in Madrasah. This type of research is qualitative with a naturalistic approach. The results showed that the principal's strategy in implementing the independent learning curriculum at Madrasah Tsanawiyah Negeri 1 Kota Gorontalo is that the principal prepares a plan for implementing the independent curriculum through meetings with teachers, the principal sends teachers to training in the form of technical guidance, webinars, seminars related to the implementation of the independent curriculum, the principal fosters teachers and students intensely, the principal builds cooperation with student parent partners. The obstacles in implementing the independent curriculum are that some teachers and students are less familiar with operating application platforms, not all teachers and students use smartphones, some teachers are elderly, school facilities are still limited, and not all parents supervise children at home in learning. Solutions in implementing the independent curriculum in madrasas, namely, encouraging more massive training on the independent curriculum, increasing the availability of facilities and infrastructure, and conducting special coaching for parents as school partners.